Expanding the recombinant protein quality in Lactococcus lactis - Cano-Garrido, Olivia (Microb Cell Fact, 2014)
BACKGROUND: Escherichia coli has been a main host for the production of recombinant proteins of biomedical interest, but conformational stress responses impose severe bottlenecks that impair the production of soluble, proteolytically stable versions of many protein species. In this context, emerging Generally Recognized As Safe (GRAS) bacterial hosts provide alternatives as cell factories for recombinant protein production, in which limitations associated to the use of Gram-negative microorganisms might result minimized. Among them, Lactic Acid Bacteria and specially Lactococcus lactis are Gram-positive GRAS organisms in which recombinant protein solubility is generically higher and downstream facilitated, when compared to E. coli. However, deep analyses of recombinant protein quality in this system are still required to completely evaluate its performance and potential for improvement. RESULTS: We have explored here the conformational quality (through specific fluorescence emission) and solubility of an aggregation-prone GFP variant (VP1GFP) produced in L. lactis. In this context, our results show that parameters such as production time, culture conditions and growth temperature have a dramatic impact not only on protein yield, but also on protein solubility and conformational quality, that are particularly favored under fermentative metabolism. CONCLUSIONS: Metabolic regime and cultivation temperature greatly influence solubility and conformational quality of an aggregation-prone protein in L. lactis. Specifically, the present study proves that anaerobic growth is the optimal condition for recombinant protein production purposes. Besides, growth temperature plays an important role regulating both protein solubility and conformational quality. Additionally, our results also prove the great versatility for the manipulation of this bacterial system regarding the improvement of functionality, yield and quality of recombinant proteins in this species. These findings not only confirm L. lactis as an excellent producer of recombinant proteins but also reveal room for significant improvement by the exploitation of external protein quality modulators.